Photosynthetic gas exchange responses to light, temperature, carbon dioxide and water stress, and changes in photosynthetic pigments to light and water stress in two cultivars of Hordeum vulgare L - Logie, Malcolme Ronald Ruxton (Rhodes University, Faculty of Science, Botany Department, 1992)
The gas exchange responses of two cultivars of Hordeum vulgare L., to light, temperature, COâ‚‚ and water stress were investigated in the laboratory. The optimum temperature for net COâ‚‚ assimilation was found to be 25Â°C and 22.5Â°C for cv. Clipper and cv. Dayan respectively. Net COâ‚‚ assimilation was reduced at 30Â°C in cv. Dayan. At low light intensity the highest quantum yield efficiency was 0.051 mol.molâ »Â¹ at 30Â°C for cv. Clipper, and 0.066 mol.molâ »Â¹ at 20Â°C for cv. Dayan. At the same temperature, cv. Clipper had a higher water use efficiency than cv. Dayan, but stomatal conductance for cv. Dayan was higher than cv. Clipper. Stomatal limitation to COâ‚‚ was lowest at the optimum temperature for COâ‚‚ assimilation in both cultivars. Stomata limited COâ‚‚ assimilation in cv. Clipper to a larger degree than in cv. Dayan. Relative stomatal limitation for cv. Clipper at 25Â°C was 0.280 Â± 0.010, and for cv. Dayan at 22.5Â°C was 0.028 Â± 0.011. Short-term exposure to elevated COâ‚‚ concentrations increased COâ‚‚ assimilation in both cultivars, but more so for cv. Clipper. Transpiration rate at elevated COâ‚‚ partial pressures were higher in cv. Dayan than in cv. Clipper. At very high COâ‚‚ (860 Î¼mol.mâ »Â²sâ »Â¹) partial pressure water use efficiency in cv. Clipper was higher than cv. Dayan, but at low COâ‚‚ partial pressures water use efficiency in cv. Dayan was higher than cv. Clipper. Water stress reduced the relative leaf water content and net COâ‚‚ assimilation in both cultivars. Cultivar Dayan was more tolerant to water stress, and COâ‚‚ assimilation in this cultivar was less affected by water stress. In both cultivars water stress increased the concentration of chlorophyll a, chlorophyll b, and chlorophyll a+b. The chlorophyll a:b ratio remained relatively constant throughout the stress period. No correlation between relative leaf water content and total carotenoid concentration was observed.
Keywords: Plants -- Photorespiration; Plants -- Transpiration; Botanical chemistry